Interactions between ocean carriers' operations and shippers' supply chain - Xu, Cen. (2009)
The current economic crisis has detrimental impacts on both global economy and international trade. As a result, both shippers and ocean carrier operations have been adversely affected. Surveys and interviews were conducted on the industry veterans to investigate the impact of the economic crisis and how they have dealt with the situation. The result shows that carriers have been improving their service quality and reducing freight rates to retain their customers. Consequently, shippers benefited from the lower transport cost and logistic cost. More shippers are also engaging in long term relationship with other players in the supply chain, including the ocean carrier and this in turn improves the supply chain performance. But besides the above strategies, very few of the shippers surveyed/interviewed have made drastic changes to their distribution strategies to cope with the current situation.